Housing policy and professional expertise in the new architectural order of “modern” Argentina (1966-1973) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this paper we intend to revisit the role played by architects as professionals in charge of designing urban projects of social interest during the dictatorship self-designated as “Argentine Revolution” (1966-1973), lead by General Juan Carlos Onganía. The task is to explore the role of such professionals in a period of “modernization and renovation” of the field of architecture, State violence and eradication of shanty towns. Due to the heterogeneity in the world of architecture, we chose to focus our analysis on the role played by the “Sociedad Central de Arquitectos” (Central Society of Architects). Our hypothesis is that the Onganiato’s foundational project that sought to consolidate a “modern Argentina” with projections for the year 2000 derived in an “urban revolution”. These plans of urban organization and infrastructure at a national scale became key for the consolidation of a “new architectural order” that coincided with business and professional demands. Thus, housing policies oriented to urban popular sectors operated as a window of opportunity for the main architecture studios, massively convened by the State.
Keywords: Argentina; Architectural; Dictatorship; Housing policy.